Construction of Discrimination Models in Prediction of Bankruptcy if Polish Non-Public Enterprises - Bernard Kokczyński (Finanse i Prawo Finansowe)
The purpose of the article. The aim of this study is to predict bankruptcy among Polish non-financial firms by constructing discriminant models and comparing the outcomes with prognostic models developed by other Polish scholars. Utilizing financial data from 2017–2021 for 416 companies across the trade, production, and service sectors, this research strives to devise the most effective model for classifying entities into two groups.